Atomic oxygen resistant composite material forming process

Through an atomic oxygen-resistant composite material molding process, the problem of composite materials that are not resistant to atomic oxygen in the aerospace environment and prone to debonding and bubbles in the pasting process is solved, and the corrosion resistance and service life of the material are extended.

CN119329176AActive Publication Date: 2025-01-21HARBIN FRP INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411713421.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-21
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Composite materials are not resistant to atomic oxygen in aerospace environment, and the adhesive process is prone to debonding and bubbles, which affects the service life.

Method used

An atomic oxygen-resistant composite material molding process is adopted, including the treatment of metal protective layer, surface treatment of resin-based carbon fiber composite material, glue configuration, metal protective layer and composite material surface glue layer coating, paving and vacuum hot pressing curing.

Benefits of technology

It effectively prevents composite materials from being denuded in an atomic oxygen environment, avoids debonding and bubble problems in the pasting process, and extends the service life of aerospace equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119329176A_ABST
    Figure CN119329176A_ABST
Patent Text Reader

Abstract

The invention discloses an atomic oxygen resistant composite material forming process. The invention belongs to the technical field of aerospace materials. The problems that in the aerospace environment, a composite material is not resistant to atomic oxygen, and debonding and bubbles are prone to occurring in the bonding process are solved. According to the preparation method, the alloy material and the resin-based carbon fiber composite material are coated with the glue solution, and then the alloy material and the resin-based carbon fiber composite material are bonded, so that the atomic oxygen resistant composite material is obtained. According to the forming process, the uniform thickness of an adhesive layer can be effectively guaranteed through rolling of the pressing roller, the metal protection layer can be better bonded to the surface of the resin-based carbon fiber composite material through the uniform adhesive layer, and it is guaranteed that the atomic oxygen-resistant composite material does not have the debonding phenomenon in the aerospace environment through the forming process; and the service life of the aerospace equipment is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerospace materials, and in particular relates to a molding process of an atomic oxygen resistant composite material. Background Art

[0002] Atomic oxygen is formed by the photolysis of oxygen molecules under solar radiation. On the one hand, atomic oxygen has strong oxidizing properties and can directly react chemically with materials. It can cause serious oxidative corrosion to organic materials and some metal materials on the surface of spacecraft, resulting in thinning of material thickness, changes in surface morphology, changes in thermal / electrical properties, and even complete failure. On the other hand, when the spacecraft is running at high speed, the energy of atomic oxygen hitting the surface of the spacecraft is very large. When these highly oxidizing, high-flux, and high-energy atomic oxygen react with the surface of the spacecraft, it will cause erosion of the surface material and degradation of performance, thereby affecting the normal operation and service life of the spacecraft. For resin composite materials and carbon fiber composite materials, they are easily affected by atomic oxygen, ultraviolet rays, etc. in the space environment, resulting in the attenuation of their physical and chemical properties, poor adaptability, and affecting the normal operation of the spacecraft. In order to ensure the long-term reliable operation of the spacecraft in orbit, the atomic oxygen resistance requirements proposed by domestic low-orbit long-life spacecraft require necessary protection for the outer components of the spacecraft.

[0003] Composite materials account for a significantly larger proportion of the structural weight of aircraft and spacecraft, and are used in a wider range of places. However, composite materials do not have the performance of atomic oxygen resistance. In order to improve this defect, the existing technology generally adopts the method of spraying, coating and pasting to cover the composite materials with a layer of anti-atomic oxygen material. However, the spraying and coating methods have serious loss and a short service life. Although the pasting method has less loss and a longer service life, it is easy to fall off or have bubbles in the pasting method, and the loss of materials affects the use. Therefore, a new process method is urgently needed to solve the problem of composite materials being attacked by atomic oxygen and the problem of debonding and bubbles in the pasting method, and to extend the service life of aerospace equipment, which is of great significance to the sustainable development of aerospace. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of composite materials being not resistant to atomic oxygen in aerospace environments, and the problems of debonding and bubbles being prone to occur in the pasting process and extending the service life of aerospace equipment. The present invention provides a molding process for composite materials resistant to atomic oxygen.

[0005] The technical solution of the present invention is as follows:

[0006] One of the purposes of the present invention is to provide a molding process for an atomic oxygen resistant composite material, wherein:

[0007] S1: Treatment of the metal protective layer: pickling the metal protective layer;

[0008] S2: Surface treatment of resin-based carbon fiber composite material: lightly polish the resin-based carbon fiber composite material with 800-1000 mesh sandpaper;

[0009] S3: Glue solution preparation: Mix epoxy glue components A and B in a mass ratio of 5:1 and place in a vacuum tank for degassing;

[0010] S4: Glue coating of metal protective layer: Cut the metal protective layer into several strips with a length of 100-500mm and a width of 50-100mm, punch a 2mm vent hole every 100mm on the central axis of the wide side, squeeze the glue evenly on the metal protective layer, and roll it evenly;

[0011] S5: coating the resin-based carbon fiber composite material with a glue layer: placing the resin-based carbon fiber composite material on a platform, adding the glue solution evenly and in small amounts multiple times to the glue coating area on the surface of the resin-based carbon fiber composite material, and rolling it evenly;

[0012] S6: Metal protective layer is laid on the surface of resin-based carbon fiber composite material: the metal protective layer is laid on the surface of resin-based carbon fiber composite material and rolled evenly. After rolling, the next metal protective layer is laid. The metal protective layers are overlapped with each other. After the laying is completed, a layer of soft film is laid on the top, put into a vacuum bag, vacuum pressurized, and then put into an autoclave for curing to obtain an atomic oxygen resistant composite material.

[0013] It is further defined that the metal protective layer in S1 is an aluminum foil or an aluminum alloy material with a thickness of 25-50 μm.

[0014] It is further defined that the vacuum tank pressure in S3 is -80 to -90 kPa, and the degassing time is 15 to 20 minutes.

[0015] It is further defined that the glue coating thickness in S4 is 10-20 μm, and the glue coating thickness in S5 is 30-40 μm.

[0016] It is further defined that the temperature of the autoclave in S6 is 45-85°C, the pressure is 200±5Kpa, and the curing time is 1-3h.

[0017] It is further defined that the overlap width between the metal protective layers in S6 is 2-10 mm.

[0018] It is further defined that the soft film in S6 is silicone rubber with a thickness of 1-2 mm, a hardness of 40-80 HB, a tensile strength of 5-10 MPa, and an elongation of 200-300%.

[0019] It is further defined that all the above steps are completed in an environment with a temperature of 15-35° C. and a relative humidity of 30%-60%.

[0020] A second object of the present invention is to provide an atomic oxygen resistant composite material prepared by the above-mentioned molding process.

[0021] A third object of the present invention is to provide an atomic oxygen resistant composite material for use in aerospace.

[0022] The beneficial effects of the present invention are as follows:

[0023] The present invention can effectively ensure the uniform thickness of the glue layer by applying glue and rolling with a special pressure roller. The uniform glue layer can better bond the metal protective layer to the surface of the composite material, realize the function of atomic oxygen resistance, and overcome the problem of bubbles appearing when the metal protective layer and the composite material are combined in a vacuum environment. After tens of thousands of high and low temperature cycles, the metal protective layer and the composite material have no debonding and no bubble generation, and can meet the 15-year service life outside the spacecraft cabin on orbit. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a vacuum autoclave;

[0025] Figure 2 This is a picture of the atomic oxygen resistant composite material of Example 1 after the vacuum autoclave test;

[0026] Figure 3 This is a picture of the atomic oxygen resistant composite material of comparative example 1 after being subjected to a vacuum autoclave test;

[0027] Figure 4 It is a graph of atomic oxygen stripping mass loss of Example 1 and Comparative Example 1;

[0028] Figure 5 This is the experimental bonding process diagram. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0031] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0032] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0033] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0035] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0036] Embodiment 1:

[0037] S1: Treatment of the metal protective layer: Select aluminum foil with a thickness of 50 μm and perform surface phosphoric acid anodizing treatment for 2 h;

[0038] S2: Surface treatment of resin-based carbon fiber composite material (carbon fiber accounts for 60% by volume, resin accounts for 40% by volume): lightly polish the surface of the composite material with 1000-grit sandpaper;

[0039] S3: Glue preparation: Mix HB01 glue, 100g of component A and 20g of component B evenly, and then put them in a vacuum tank for degassing. The pressure of the vacuum tank is -90kpa, and the degassing time is 20min.

[0040] S4: Glue coating of metal protective layer: Cut the metal protective layer into several strips with a length of 500 mm and a width of 100 mm, punch a 2 mm vent hole every 100 mm on the central axis of the wide side, adhere green high temperature resistant pressure sensitive tape on both sides of the metal protective layer, place the metal protective layer on the metal plate, make the side with the pressure sensitive tape fit the metal plate, squeeze the glue evenly on the metal protective layer, the glue coating thickness is 20 μm, and roll it evenly;

[0041] S5: Coating the resin-based carbon fiber composite material glue layer: Place the resin-based carbon fiber composite material on the platform, add the HB01 glue solution twice evenly, add it to the surface of the resin-based carbon fiber composite material, roll it evenly, and the glue coating thickness is 40 μm;

[0042] S6: metal protective layer covering the surface of resin-based carbon fiber composite material: placing the metal protective layer on the surface of the resin-based carbon fiber composite material, and rolling it with a 100mm rubber roller. After rolling, tear off the pressure-sensitive tape, and lay the next metal protective layer. The metal protective layers are overlapped with each other, and the overlap width is 5mm. After the paving is completed, a layer of soft film material is laid on the top, put into a vacuum bag, vacuum pressurized, and then added to the autoclave for curing. The autoclave temperature is 80°C, the pressure is 200±5KPa, and the curing time is 2h to obtain an atomic oxygen resistant composite material;

[0043] All the above steps are completed in a 100,000-class clean room with an ambient temperature of 26°C and a relative humidity of 40%.

[0044] Comparative Example 1:

[0045] S1: Treatment of the metal protective layer: Select aluminum foil with a thickness of 15 μm and perform surface polishing;

[0046] S2: Surface treatment of resin-based carbon fiber composite materials: lightly polish the surface of the composite material with 600-grit sandpaper;

[0047] S3: Glue preparation: Mix HB01 glue, 100g of component A and 20g of component B evenly;

[0048] S4: Metal protective layer adhesive coating: squeeze the adhesive evenly on the metal protective layer, the coating thickness is 100μm, and roll it evenly;

[0049] S5: Coating of resin-based carbon fiber composite adhesive layer (carbon fiber accounts for 60% by volume, resin accounts for 40% by volume): Place the resin-based carbon fiber composite material on the platform, add HB01 glue solution to the surface of the resin-based carbon fiber composite material at one time, roll it evenly, and the coating thickness is 100 μm;

[0050] S6: Laying the metal protective layer on the surface of the resin-based carbon fiber composite material: placing the metal protective layer on the surface of the resin-based carbon fiber composite material, and after the paving is completed, putting it into a vacuum bag, pressurizing the vacuum bag, maintaining the vacuum pressure at -85kpa, and curing time 24h to obtain an atomic oxygen resistant composite material;

[0051] All the above steps are completed in a 100,000-class clean room with an ambient temperature of 26°C and a relative humidity of 40%.

[0052] Vacuum autoclave test:

[0053] The experimental conditions are ±100℃, vacuum degree 10 -4 , the number of cycles is 12 times.

[0054] Depend on Figure 2 and Figure 3 It can be explained that after the thermal vacuum test, the surface of Example 1 treated by the experimental process is still flat, no bubbles are generated, and no protrusions are produced, showing excellent material properties, while the test piece of Comparative Example 1 that has not been treated by the experimental process has many bubbles and wrinkles on the surface.

[0055] Atomic oxygen stripping mass loss test:

[0056] Experimental conditions: The atomic oxygen irradiation test was carried out on a plasma-type atomic oxygen ground simulation device. The oxygen plasma was generated by the magnetic mirror configuration microwave ECR method. The atomic oxygen energy was 5 eV; the flux rate was 5.0×1015O / (cm 2 ·s); when the irradiation dose reaches 10.0×1020O / cm 2 When testing the performance of the material, the test results are as follows: Figure 4 As shown by Figure 4 It can be seen that the atomic oxygen stripping mass loss of Example 1 is only 0.1%, while the atomic oxygen stripping mass loss of Comparative Example 1 is 0.8%, which shows that the atomic oxygen-resistant composite material treated by this experimental process can effectively resist the erosion of atomic oxygen in space and meet the use requirements of spacecraft materials.

[0057] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A process for forming an atomic oxygen resistant composite material, characterized in that: The molding process comprises the following steps: S1: Treatment of the metal protective layer: pickling the metal protective layer; S2: Surface treatment of resin-based carbon fiber composite material: lightly polish the resin-based carbon fiber composite material with 800-1000 mesh sandpaper; S3: Glue solution preparation: Mix epoxy glue components A and B in a mass ratio of 5:1 and place in a vacuum tank for degassing; S4: Glue coating of metal protective layer: Cut the metal protective layer into several strips with a length of 100-500mm and a width of 50-100mm, punch a 2mm vent hole every 100mm on the central axis of the wide side, squeeze the glue evenly on the metal protective layer, and roll it evenly; S5: coating the resin-based carbon fiber composite material with a glue layer: placing the resin-based carbon fiber composite material on a platform, adding the glue solution evenly and in small amounts multiple times to the glue coating area on the surface of the resin-based carbon fiber composite material, and rolling it evenly; S6: Metal protective layer is laid on the surface of resin-based carbon fiber composite material: the metal protective layer is laid on the surface of the resin-based carbon fiber composite material and rolled evenly. After the rolling is completed, the next metal protective layer is laid. The metal protective layers are overlapped with each other. After the laying is completed, a layer of soft film is laid on the top, put into a vacuum bag, vacuum pressurized, and then added to the autoclave for curing to obtain an atomic oxygen resistant composite material.

2. The molding process according to claim 1, characterized in that: The metal protective layer in S1 is made of aluminum foil or aluminum alloy material with a thickness of 25-50 μm.

3. The molding process according to claim 1, characterized in that: The vacuum tank pressure in S3 is -80~-90kpa, and the degassing time is 15-20min.

4. The molding process according to claim 1, characterized in that: The glue coating thickness in S4 is 10-20μm, and the glue coating thickness in S5 is 30-40μm.

5. The molding process according to claim 1, characterized in that: The temperature of the autoclave in S6 is 45-85°C, the pressure is 200±5Kpa, and the curing time is 1-3h.

6. The molding process according to claim 1, characterized in that: In S6, the overlap width between the metal protective layers is 2-10 mm.

7. The molding process according to claim 1, characterized in that: The S6 medium soft film is silicone rubber with a thickness of 1-2mm, a hardness of 40-80HB, a tensile strength of 5-10 MPa, and an elongation of 200-300%.

8. The molding process according to claim 1, characterized in that: All the above steps are completed in an environment with a temperature of 15-35°C and a relative humidity of 30%-60%.

9. An atomic oxygen resistant composite material, characterized in that: Prepared by the molding process described in any one of claims 1 to 8.

10. The atomic oxygen resistant composite material according to claim 9 is used in aerospace.

Citation Information

Patent Citations

  • Tension-compression balance composite structure of composite material and manufacturing method thereof

    CN112644102A

  • High-performance aluminum alloy-carbon fiber reinforced resin-based composite material and preparation method thereof

    CN114801365A